Analisis Hukum Normatif terhadap Pengujian Permendikbud Nomor 82 Tahun 2015 tentang Penanganan Kekerasan di Sekolah oleh Kekuasaan Kehakiman dalam Perspektif Kasus Bullying - Surya Pratama Erlangga; Mochammad Hoshi Lazuardy; Maulana Dzaky Akmal P; Sabrina Zahro Wardah Azkiyah; Venia Sonarista (VJJ, 2025)
Bullying in educational settings remains a persistent problem that threatens students’ psychological safety and disrupts the learning environment. Although Indonesia has established legal frameworks for child protection, schools often face challenges in translating these broad norms into clear operational procedures. This paper examines the normative position of the Indonesian Ministry of Education and Culture Regulation Number 82 of 2015 concerning the Prevention and Handling of Violence in Schools and evaluates its potential to be reviewed by judicial authorities when applied in administrative decision-making. Using a normative legal research method, the study analyzes statutory regulations, scholarly literature, and relevant administrative principles to assess the legal status, effectiveness, and limitations of the regulation within the national legal system. The findings indicate that the regulation serves as an important administrative instrument that guides schools in preventing, responding to, and documenting bullying cases. However, its implementation remains uneven due to varying institutional capacities, limited understanding of procedural standards, and the absence of consistent monitoring mechanisms. The study further reveals that although ministerial regulations do not occupy a formal position in the statutory hierarchy, their application can still be subject to judicial review through administrative courts when they serve as the basis for decisions affecting students’ rights. This research concludes that Regulation 82/2015 plays a significant role in strengthening school-based protection mechanisms but requires continuous refinement, stronger institutional support, and harmonization with higher legal norms to ensure effective and accountable handling of bullying cases. Keywords: Bullying; Education; Law; Child Protection; School